2015
DOI: 10.5194/acp-15-8781-2015
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of secondary organic aerosol tracers in Central Tibetan Plateau

Abstract: Abstract. Secondary organic aerosol (SOA) affects the earth's radiation balance and global climate. High-elevation areas are sensitive to global climate change. However, at present, SOA origins and seasonal variations are understudied in remote high-elevation areas. In this study, particulate samples were collected from July 2012 to July 2013 at the remote Nam Co (NC) site, Central Tibetan Plateau and analyzed for SOA tracers from biogenic (isoprene, monoterpenes and β-caryophyllene) and anthropogenic (aromati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 56 publications
5
53
0
Order By: Relevance
“…5d) while the lowest during winter. Their seasonal variation was in agreement with the ambient temperature (Fig S1a), which can influence the isoprene emissions and the photochemical processes (Shen et al, 2015;Wang et al, 2008). The annual average concentration was higher than the 400 urban sites reported from Beijing (44.3 ng m -3 ) and Kunming (108 ng m -3 ) (Ding et al, 2016a), even one to two orders of magnitude higher than that from global oceans and the Arctic (Hu et al, 2013).…”
Section: The Measurements Of Gaseous Vocs In Winter (December 2012 Tosupporting
confidence: 56%
See 2 more Smart Citations
“…5d) while the lowest during winter. Their seasonal variation was in agreement with the ambient temperature (Fig S1a), which can influence the isoprene emissions and the photochemical processes (Shen et al, 2015;Wang et al, 2008). The annual average concentration was higher than the 400 urban sites reported from Beijing (44.3 ng m -3 ) and Kunming (108 ng m -3 ) (Ding et al, 2016a), even one to two orders of magnitude higher than that from global oceans and the Arctic (Hu et al, 2013).…”
Section: The Measurements Of Gaseous Vocs In Winter (December 2012 Tosupporting
confidence: 56%
“…5). Though the major emissions of aromatics come from solvent and fossil fuel use, biomass burning is also considered as an possible source 465 in some sites of the world (Shen et al, 2015). There was a good correlation between DHOPA and levoglucosan ( Fig.…”
Section: Aromatic Soa Tracermentioning
confidence: 78%
See 1 more Smart Citation
“…Analytical procedures were described in detail in a previous study (Ding et al, 2012), and are provided in the Supporting Information. The relative standard deviation (RSD) for this reconstructed SOC in our lab was 51 ± 11% (Shen et al, 2015).…”
Section: Chemical Analysismentioning
confidence: 86%
“…3), MO-OOA was likely closely related to long-range transport of air mass from southwest, while LO-OOA could be derived from relatively shorter distance transport such as from a marine air mass from south and regional background aerosol during the nighttime. Shen et al (2015) reported that there was a significant aerosol source from biogenic emissions during summer near the Nam Co station. As shown in Fig.…”
Section: The Pmf Apportionment On the Oamentioning
confidence: 99%